First principles study of structural and magnetic properties of transition metal nitrides TMN (TM = Cr, Mn). (2nd September 2017) - Rajeswarapalanichamy, R.; Amudhavalli, A.; Manikandan, M.; Kavitha, M.; Iyakutti, K.
ABSTRACT: The structural stability of chromium nitride (CrN) and manganese nitride (MnN) is investigated among four different structures, namely, NaCl (Fm3m), zinc blende (F4-3m), orthorhombic (Pnma) and tetragonal (I4/mmm). It is found that the most stable phase is the zinc blende phase for CrN and MnN. The structural phase transition from zinc blende to orthorhombic phase is predicted at high pressure. At normal pressure, CrN and MnN are found to be antiferromagnetic. As the pressure is increased, antiferromagnetic-to-nonmagnetic phase transition is observed at the pressures of 169.5 GPa in CrN and 206 GPa in MnN. The elastic constants obey the Born--Huang criteria, suggesting that they are mechanically stable. The calculated B / G values indicate that CrN and MnN are ductile in nature.